Creative Inquiry in Soil Science: Soil Inventory of Private Lands. Issue 1 (18th December 2015) - Mikhailova, E. A.; Post, C. J.; Sharp, J. L.; Speziale, B. J.
Abstract : Creative Inquiry (CI) projects provide unique learning opportunities in soil science education. Clemson University's CI program combines engaged learning and undergraduate research. We have developed a highly effective hands‐on CI project involving soil inventory of private lands using the Web Soil Survey to identify soil map units, collected soil samples in the field, analyzed them in the Clemson University Agricultural Service Laboratory, and interpreted the soil testing results for management recommendations. Clemson University students from various fields (forestry, wildlife biology, environmental science, agricultural education, etc.) have conducted soil inventories of private lands in the Forestry and Natural Resources (FNR) class FNR 4700: GIS and SIS Applications course taught from 2007 to 2015 (60 students total). Students were asked to fill out a survey (2013, 2014, and 2015) consisting of questions related to their learning experience and the usefulness of their CI project, as well as to their overall satisfaction with the CI program. Responses to the survey questions indicated that the CI project improved the student's confidence in successfully performing various research tasks. Students strongly agreed that teaching undergraduates how to conduct research should be an important goal of the university. Overall, student responses to the questionnaire about their CI project experience were positive, indicating that incorporating project‐based learning can enhance soil science education. Impact Statement Creative inquiry (CI) projects provide unique learning opportunities in soil science. The Clemson University CI program combines engaged learning and undergraduate research. This article describes an example of creative inquiry–based project in undergraduate soil science education. A post‐project survey of the students indicated that students were very confident to successfully perform various research tasks, and they strongly agreed that teaching undergraduates how to conduct research should be an important goal of the university.